Effect Of Standardised Methanolic Extract Of Phyllanthus Niruri (Linn.) On Phase I And II Drug Metabolism And Its Molecular Mechanism Elucidation In Rat Liver - Bashir, Moath Kahtan (2010)
Phyllanthus niruri (P. niruri) is a widely available medicinal plant in tropical and subtropical regions of the world. In Malaysia, it is locally known as “Dukong Anak”. Many therapeutic effects of this plant have been reported including antiviral effects especially on hepatitis B and human immune deficiency virus (HIV), antihyperuricemic, removal of kidney and gall stones, anti-nociceptive, anti-inflammatory, anti-hyperlipemic, anti-hypertensive, anti-parasitic and anti-microbial activities. Phytochemical studies of this plant showed diversity of chemical contents such as lignans, alkaloids, flavonoids, sterols, coumarins, benzenoids, tannins, and triterpenes. Due to the wide use of herbal medicinal products, the possibilities of herb-drug interactions have increased. Little is known about the incidence and consequences of herb-drug interactions in patients who consume P. niruri concomitantly with other drugs. The aims of this study were to investigate the in vitro and ex vivo effects of standardized methanolic extract of P. niruri on phase I and II metabolizing enzymes in rat liver under the influence of diseases (diabetes and hypertension), gender, and age, as well as to elucidate the molecular mechanism by which it affect aminopyrine phase I metabolism. The in vitro study found that standardized methanolic extract of P. niruri did not show significant effect on phase I aminopyrine metabolism in normal rats of different gender and age groups while the extract at the higher concentration (10 μg/mL) showed significant induction effect on diabetic rats and spontaneously hypertensive rats.